The relationship between healthcare expenditure and disposable personal income in the US states: A fractional integration and cointegration analysis - Guglielmo Maria Caporale; Juncal Cunado; Luis A. Gil-Alana; Rangan Gupta (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This study examines the relationship between healthcare expenditure and disposable income in the 50 US states over the period 1966-2009 using fractional integration and cointegration techniques. The degree of integration and nonlinearity of both series are found to vary considerably across states, whilst the fractional cointegration analysis suggests that a long-run relationship exists between them in only 11 out of the 50 US states. The estimated long-run income elasticity of healthcare expenditure suggests that health care is a luxury good in these states. By contrast, the short-run elasticity obtained from the regressions in first differences is in the range (0,1) for most US states, which suggests that health care is a necessity good instead. The implications of these results for health policy are also discussed.
Keywords: C22; C32; H51; I18; 330; healthcare expenditure; income elasticity; US states; fractional integration; fractional cointegration